The relationship between intolerance of uncertainty, coping style, resilience, and anxiety during the COVID-19 relapse in freshmen: A moderated mediation model - Wang, Ting; Jiang, Lingwei; Li, Tiantian; Zhang, Xiaohang; Xiao, Sanrong (Frontiers in Psychiatry, 2023)
Background The repeated outbreaks of COVID-19 and the rapid increase in uncertainty have had many negative effects on the public’s mental health, especially on emotional aspects such as anxiety and depression. However, in previous studies, there are few studies exploring the positive factors between uncertainty and anxiety. The innovation of this study is the first to explore the mechanism of coping style and resilience as people’s psychological protective factors between uncertainty and anxiety caused by the COVID-19 pandemic. Methods This study explored the relationship between intolerance of uncertainty and anxiety of freshmen with coping style as mediating variable and resilience as moderating variable. A total of 1049 freshmen participated in the study and completed the Intolerance of Uncertainty Scale (IUS-12), Self-rating Anxiety Scale (SAS), Simplified Coping Style Questionnaire (SCSQ), and Connor-Davidson Resilience Scale (CD-RISC). Results SAS score of the surveyed students (39.56 ± 10.195) was significantly higher than that of the Normal Chinese score (29.78 ± 10.07, p < 0.001). Intolerance of uncertainty was significantly positively correlated with anxiety (β = 0.493, p < 0.001). Positive coping style has a significant negative impact on anxiety (β = −0.610, p < 0.001), negative coping style has a significant positive impact on anxiety (β = 0.951, p < 0.001). Resilience moderates the second half of the influence of negative coping style on anxiety (β = 0.011, t = 3.701, p < 0.01). Conclusion The findings suggest that high levels of intolerance of uncertainty had negative effects mental burden during the COVID-19 pandemic. The knowledge of the mediating role of coping style and the moderating role of resilience may be used by health care workers when consulting freshmen with physical health complaints and psychosomatic disorders.